Durban Harbour Tunnel—First Use of a Slurry Tunnel Boring Machine in South Africa - J. Andrew Hindmarch; A. L. Griffiths; Andrew K. hg` Officer; Gert Wittneben (Society for Mining, Metallurgy & Exploration, 2007)
Durban Harbour in South Africa is one of the continent’s busiest ports however the harbor entrance is currently too small for the new generation of container ships. There-fore it is to be deepened and widened by the National Ports Authority in the near future. An existing immersed tube tunnel carrying major sewer, water and other utilities under the harbor first needs to be removed and replaced by a deeper 4.4 m ID ser-vices tunnel. Construction of the deeper tunnel saw the first use of a slurry machine in South Africa and was required to negotiate grades up to 20%.